Platform pricing under dispersed information - Bruno Jullien; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2014)
We study monopoly and duopoly pricing in a two-sided market with dispersed information about users' preferences. First, we show how the dispersion of information introduces idiosyncratic uncertainty about participation rates and how the latter shapes the elasticity of the demands and thereby the equilibrium prices. We then study informative advertising campaigns affecting the agents' ability to estimate their own as well as other agents' valuations, and product design affecting the distribution of valuations on the two sides of the market.
Keywords: D82; 330; two-sided markets; dispersed information; platform competition; global-games; informative advertising